PERANCANGAN SMART TRASH BIN MENGGUNAKAN LOGIKA FUZZY BERBASIS ARDUINO DI SDN 5 MAWASANGKA, BUTON TENGAH - Nurjannah, Nurjannah; Muchtar, Mutmainnah; Sarimuddin, Sarimuddin; Sya'ban, Kharis; Karim, Rahmat; Al Jum'ah, Muhammad Na'im (Jurnal Informatika dan Teknik Elektro Terapan, 2024)
Smart Trash Bin is a technological innovation that integrates sensors and automation systems to enhance waste management efficiency. This study aims to design and implement a Smart Trash Bin using fuzzy logic based on Arduino at SDN 5 Mawasangka, Buton Tengah. In this research, the system utilizes ultrasonic sensors to detect the trash level inside the bin, servo motors to control the automatic lid of the trash bin, and DFPlayer Mini along with a speaker to provide audio notifications to users. Fuzzy logic method is employed to regulate the system's decisions in managing the trash bin operations based on environmental conditions. The study involves the stages of design, fabrication, and system testing in the elementary school environment. The test results indicate that the designed Smart Trash Bin can effectively manage waste with adequate accuracy. It is expected that the implementation of this Smart Trash Bin can help raise awareness of environmental cleanliness within the school and surrounding community